Isolation and characterization of the product of the methionine-regulatory gene metJ of Escherichia coli K-12. - Smith, A A (Proc Natl Acad Sci U S A, 1985)
We have modified a previously isolated metJ plasmid by removing a segment of DNA including the rop gene. Bacterial strains carrying this plasmid produce elevated levels of the metJ gene product, presumably because of the high number of gene copies in the cell. We have isolated the metJ gene product in nearly homogeneous form from such a strain. The subunit size and the amino acid composition are the same as those predicted from the DNA sequence of the metJ gene. Sedimentation equilibrium measurements show that the native metJ gene product is a dimer. The purified dimer protects a short segment of DNA in the regulatory region of the metB and metJ genes from hydrolysis by DNase I. IMAGES: